Learning Rational Numbers through an Emergent Modeling Process enhanced by Percentage - Guerreiro, Helena Gil (2020)
In this paper, a discussion about how elementary students’ conceptual understanding of rational numbers is fostered, along with number sense development, in a sociocultural learning perspective, is carried out. We highlight how an emergent modeling process, enhanced by percentage and supported by multiple representations, emphasizing numerical values of magnitude contexts, may contribute to that understanding. A classroom experiment was developed, following the methodological procedures of a Design Research. We analyze student’s interactions and their work, as representations are used and transformed as models. Findings suggest that percentage, associated to students’ real world experiences and previous knowledge, is intuitive and seems to be helpful in students’ numerical development from whole numbers to rational numbers. In a classroom community that supports a co-participated learning, where multiple representations serve and become models as dynamic process, can be a way to reach the meaning of rational number’s concepts and to strength interrelationships between those concepts.